UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN LAYANAN BIMBINGAN KELOMPOK BERBANTUAN EXPRESSIVE WRITING PADA SISWA KELAS VII A SMP 1 BAE TAHUN PELAJARAN 2022/2023 - Widanto, Fadhal; Sucipto, Sucipto; Kusmanto, Agung Slamet (Universitas Muria Kudus, 2024)
The purpose of this research is improve student learning motivation in grade VII A students of SMP 1 Bae Kudus in academic years 2022/2023 before and after using guidance and group consulting services and to understanding the steps of student motivation learning using expressive writing technique able to improve students learning motivation in grade VII A students of SMP 1 Bae Kudus in academic years 2022/2023. This research is group consulting research consist of two cycles. Each cycle consist of 4 steps; planning, action, observation, and reflection. The Subject of this research is the students of grade VII A numbering 10 students. This research is group consulting research consist of two cycles. The Result of the research showed score obtained in students learning motivation increased by 12 from the initial score obtained during the pre-cycle, the average score was 9 with the Very Poor (VP), Cycle I average score was 14 with the enough (E) Category, and in cycle II the average score was 21 with the Excellent (EX) Category. Conclusion of this research is the students learning motivation can be improved after application guidance and group consulting services with expressive writing technique to class grade VII A Students of SMP 1 Bae Kudus as evidenced by the result of collaborator observations of the researcher in the implementation of cycle I obtained an average score 55 in the Poor (P) category. Cycle II obtained an average of 88 with the Excellent (EX) Category). So Guidance and group consulting services using expressive writing technique carried out by researcher from cycle I to cycle II increased by an average of 33.